1990
DOI: 10.1038/ki.1990.203
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection in two urban hemodialysis units

Abstract: We determined the prevalence of antibodies to the hepatitis C virus (anti-HCV) in 90 patients and 37 staff members of two hemodialysis units utilizing a recently developed anti-HCV recombinant based assay. Eleven patients (12%) were anti-HCV(+). Of these, eight (73%) had antibodies to the hepatitis B core antigen (anti-HBc) indicating prior hepatitis B infection; one patient was hepatitis B surface antigen (HBsAg)(+). All staff members were anti-HCV(-), although seven (19%) of them were anti-HBc(+). Alanine am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1
8

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 10 publications
5
48
1
8
Order By: Relevance
“…Therefore, strict adherence to universal precautions and careful attention to hygiene are recommended to reduce the transmission of HCV in dialysis units. [21], [11] Contradictory to our finding, other studies show prevalence of 1-28%. [1], [21], [11], [26], [17] This low prevalence can be attributed to the fact that the risk of acquiring HCV infection in haemodialysis units has decreased partially after the isolation of HCV positive patients in separated haemodialysis units.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, strict adherence to universal precautions and careful attention to hygiene are recommended to reduce the transmission of HCV in dialysis units. [21], [11] Contradictory to our finding, other studies show prevalence of 1-28%. [1], [21], [11], [26], [17] This low prevalence can be attributed to the fact that the risk of acquiring HCV infection in haemodialysis units has decreased partially after the isolation of HCV positive patients in separated haemodialysis units.…”
Section: Discussionsupporting
confidence: 56%
“…[4] The mean duration of haemodialysis was two years compared to other studies which showed higher mean duration of six years by Mohammed Ali et al and 7.2 years by Jeffers et al [22], [21] HCV was found to be more prevalent among patients who had undergone haemodialysis for a longer duration owing to greater exposure over the years.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Entre pacientes sob hemodiálise, a prevalência da infecção pelo VHC, reconhecida pela presença do seu anticorpo (anti-VHC), varia de 1 a 48%, de acordo com vários estudos (4,14,18,23) .…”
Section: Introductionunclassified
“…The recent development of assay methods for hepatitis C virus (HCV) infection has revealed that HCV infections is highly prevalent (11–25%) in patients under maintenance hemodialysis [1, 2, 3, 4, 5]. HCV infection progresses to chronic hepatitis in 50–60% of cases [6], resulting in liver cirrhosis in 20–30 years [7].…”
Section: Introductionmentioning
confidence: 99%